KAJIAN LITERATUR PERBANDINGAN TEKNOLOGI LORAWAN DAN NB-IOT PADA SISTEM SMART AGRICULTURE BERBASIS INTERNET OF THINGS - Raihan Riyon Pratama; Andi Ahmad Dahlan; Ramiati Ramiati; Yulindon Khaidir (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The development of the Internet of Things (IoT) has encouraged the implementation of smart agriculture systems through the integration of sensors, communication technologies, and automated monitoring systems. Communication technology plays an important role in supporting long-range data transmission with low power consumption and efficient implementation costs. Two Low Power Wide Area Network (LPWAN) technologies widely used in IoT-based smart agriculture are LoRaWAN and Narrowband Internet of Things (NB-IoT). This study aims to analyze and compare the characteristics, performance, advantages, limitations, and implementation of LoRaWAN and NB-IoT through a literature review approach. Scientific articles published between 2021 and 2026 were collected from Google Scholar, IEEE Xplore, ScienceDirect, MDPI, and Springer. The analysis focused on communication coverage, power consumption, latency, scalability, infrastructure requirements, implementation costs, reliability, and suitability for smart agriculture. The results show that LoRaWAN is more suitable for low-power and low-cost monitoring systems, while NB-IoT provides better communication stability and quality of service for real-time applications.